Peran Apron Movement Control (AMC) Dalam Menerapkan Kedisiplinan Kerja Karyawan Di Bandar Udara Internasional Sultan Hasanuddin Makassar - Nurifi Nurifi; Elisabeth Endang Prakosawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Air transportation is the primary choice due to its speed, safety, and comfort. Airports are places where aircraft land and take off and conduct various activities related to passengers and cargo, categorized into domestic and international. The Apron Movement Control (AMC) unit at PT Angkasa Pura I oversees movements in the apron area and provides services to airport users. Strict supervision is required to maintain safety and discipline on the apron. However, observations at the AMC at Sultan Hasanuddin International Airport in Makassar show a lack of discipline among staff, such as oil spills on the apron, which pose a safety hazard. This research aims to understand the role of AMC in enforcing employee discipline and the challenges faced at Sultan Hasanuddin International Airport in Makassar. This research employs a qualitative approach to understand the phenomena in the Apron Movement Control unit at PT Angkasa Pura I, Sultan Hasanuddin International Airport in Makassar, from June 1 to July 31, 2024. Primary data were collected through interviews and direct observations, while secondary data were obtained from company documents and literature studies. Data analysis involves reduction, presentation, and conclusion drawing, with data validity tested through source, technique, and time triangulation. Research steps include interviews, observations, data analysis, and conclusion drawing.The results show that the Apron Movement Control (AMC) unit at Sultan Hasanuddin International Airport in Makassar plays a crucial role in maintaining security, order, and discipline on the apron. They control the movements of aircraft, vehicles, and personnel and ensure operations follow safety procedures. AMC also acts as disciplinarian and educator through regular training. However, they face challenges such as a lack of employee understanding of procedures, limited communication equipment, communication challenges due to noise, and high operational pressure. To overcome these challenges, AMC needs to strengthen training, improve communication and coordination, enhance facilities, and increase employee welfare. These measures are expected to improve AMC's performance and instill a strong work discipline culture, making them the front line in maintaining airport security and operational efficiency.